Stability of Rehydrated Mycoplasma gallisepticum Vaccine Homogeneity over Time - Leigh , Spencer A.; Evans, Jeff D.; Branton, Scott L. (International Journal of Poultry Science, 2014)
Proper vaccine application is required to maximize the results of the vaccination, while maintenance of a homogenous vaccine solution is critical to obtain uniform results. This study was designed to analyze the need for continuous mixing of rehydrated Mycoplasma gallisepticum vaccine solution in order to maintain a homogeneous solution during vaccine application. Commercial F-strain vaccine (AviPro® MG F) was rehydrated and diluted in phosphate buffered saline in accordance with field practices. Dextrose was added to the solution to maintain M. gallisepticum viability without growth during the experiment. The vaccine solution was poured into columns and samples from the static solution were taken from 1, 25 and 50 cm above the base of the column. Samples were taken at 15, 30, 60 and 120 min and compared to a control that was mixed prior to sampling. The results indicate that no significant change in vaccine concentration occurred over the course of the experiment when comparing the mixed control to any of the samples. These results suggest that there is no need for continuous M. gallisepticum vaccine mixing if vaccine is applied within 2 h.